Agentic AI Adoption: Balancing Enthusiasm and Ethical Concerns An Exploratory Study - Nadia Azaria; Mambang Mambang; Finki Dona Marleny; Trifebi Shina Sabrila (Politeknik Negeri Batam, 2026)
Agentic AI represents a significant paradigm shift in artificial intelligence, transitioning from passive command execution to autonomous goal pursuit. This exploratory study investigates user perceptions toward Agentic AI adoption in Indonesia, focusing on the balance between functional enthusiasm and ethical concerns. The 20 Likert-scale statements were developed based on the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and AI trust frameworks. These items cover key dimensions including perceived usefulness, ease of use, trust in autonomy, productivity enhancement, data privacy, loss of human control, algorithmic bias, and adoption intention. Utilizing Exploratory Data Analysis (EDA) supplemented with non-parametric tests on a convenience sample of 22 respondents predominantly tech-savvy young adults this study reveals high familiarity with AI tools (54.5% daily users). Respondents showed strong optimism regarding productivity and efficiency (Positive Aspects mean = 3.52), while maintaining notable ethical concerns (Concern Aspects mean = 3.64). The instrument demonstrated excellent reliability (Cronbach’s Alpha = 0.921 overall). Mann-Whitney U tests indicated significant gender differences on certain items, particularly bias concerns. Due to the small sample size and self-selection bias, findings should be interpreted cautiously. This study provides preliminary insights and highlights the need for human-centric design, transparent governance, and culturally appropriate regulations to support responsible Agentic AI adoption in Indonesia.